2016
DOI: 10.1080/02640414.2016.1183808
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of recovery from a 161-km ultramarathon

Abstract: The primary study objective was to identify determinants of short-term recovery from a 161-km ultramarathon. Participants completed 400 m runs at maximum speed before the race and on days 3 and 5 post-race, provided a post-race blood sample for plasma creatine kinase (CK) concentration, and provided lower body muscle pain and soreness ratings (soreness, 10-point scale) and overall muscular fatigue scores (fatigue, 100-point scale) pre-race and for 7 days post-race. Among 72 race finishers, soreness and fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 18 publications
1
21
0
Order By: Relevance
“…For the subsample of 8 subjects who performed the pre-race 400-m runs, their times at 10 days after the race were statistically similar to pre-race times, although mean times were still ~5% slower at 10 days after the race. Our prior work at the WSER had also demonstrated that muscle pain and soreness ratings had statistically returned to baseline by post-race day 5, but 400-m run times were not examined in that study beyond post-race day 5 at which time pre-race performance had not been fully recovered [3]. In the present work, we extended the post-race time period of examination to 10 days and found that this appears to be close to the timeframe of 400-m run recovery.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the subsample of 8 subjects who performed the pre-race 400-m runs, their times at 10 days after the race were statistically similar to pre-race times, although mean times were still ~5% slower at 10 days after the race. Our prior work at the WSER had also demonstrated that muscle pain and soreness ratings had statistically returned to baseline by post-race day 5, but 400-m run times were not examined in that study beyond post-race day 5 at which time pre-race performance had not been fully recovered [3]. In the present work, we extended the post-race time period of examination to 10 days and found that this appears to be close to the timeframe of 400-m run recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has been previously used at the WSER [27] and elsewhere [39], and the values have been found to correlate with plasma CK concentrations [35]. Ratings were provided at race registration, during the race at the 48-, 90-, and 126-km checkpoints, at the finish prior to the blood draw, and each morning of the 10 days following the race after being up and moving around for approximately 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations